Compressive behavior of concrete-encased CFST column with initial stress. (February 2023) - He, Fuyun; Li, Cong; Chen, Baochun; Liu, Junping; Zhang, Mengjiao; Briseghella, Bruno
Abstract: Concrete-encased CFST (CE-CFST) member refers to a hybrid structure consisting of outer reinforced concrete and inner CFST components. This paper studies the compressive behavior of CE-CFST stub columns with initial stress on steel tube. Nine compression tests on CE-CFST stub columns were completed. The influences of initial stress degree and eccentricity on the failure mode, load-displacement behavior and ultimate strength were investigated. The crushed concretes with locally buckled longitudinal rebars were observed at the middle height of specimens. The ultimate strength of CE-CFST stub column slightly decreases as initial stress degree increasing. The maximum decreasing range on the ultimate compressive strength was 9.3% as the initial stress degree increasing in range of 0–0.5. A finite element model of CE-CFST stub column was developed and verified against test results. The parameters study and full-range compression process analysis were performed using the verified finite element model. The strength contribution provided by the inner CFST and outer RC components and interactions between concretes and steel tube were discussed. The influence mechanism of initial stress on the compressive behavior of CE-CFST stud column was revealed by the test and finite element results. The constraint effect on the core concrete provided by steel tube decreased due to the presence of initial stress, which reduced the strength contribution of the CFST component to the CE-CFST column. A simplified method was proposed to predict the influence coefficient of initial stress on the ultimate strength of the CE-CFST column based on the test and finite element results. Highlights: Compression tests of CE-CFST stud column with initial stress on steel tube were completed. Finite element analysis of CE-CFST stud column with initial stress on steel tube was realized. The influence mechanism of initial stress on compressive behavior of CE-CFST column was revealed. The influence coefficient of initial stress on ultimate strength of CE-CFST column was proposed.